Experimental study on transforming dredged silt from water systems into roadbase filling - SHAO Yu-fang (浙江大学学报. 农业与生命科学版, 2005)
A method was presented to treat the dredged silt from water systems with soil stabilizer so that the soils became suitable for roadbase construction. Two soil samples, namely silt (soil a) and silty clay (soil b) dredged from the Hangzhou-Ningbo Canal, with different stabilizer/soil ratios were first shaped into cylinders 5 cm in both diameter and height. Then unconfined compression tests were conducted to measure the strength increase of the stabilized soil and determine the optimal stabilizer/soil mixing ratio. Results showed that the confined compression strength (qu) of both soil samples was effectively enhanced. When the mixing ratio aw≥4%, both of the two stabilized-soils can be used as subbase filling of road, and when aw≥10%, only stabilized soil a can be used as roadbase filling. So long as aw<2%, the stress-strain (σ-ε) curves of the two stabilized soil samples were almost identical to that of the original soils, which were work hardening. As aw≥2%, σ-ε curves of the two stabilized soils turned into work softening. The curves also revealed that the stabilizer was capable of reducing the brittleness and increasing the plasticity of soil a, with, however, an opposite effect on soil b. Through field tests, the method was proved to be economically and technically feasible.